Contested allegiances: Indian South Africans, passive resistance, and the 1947 royal visitto South Africa (Historia, 2021)
This article examines the responses of the Indian South African community towards the 1947 British royal visit to South Africa. Following World War II, the African and Indian populations of South Africa were engaging in increasingly militant or "radical" political agendas. The Natal Indian Congress (NIC) encouraged a boycott of the royal visit as early as September 1946, citing its current participation in a passive resistance campaign targeting racist and discriminatory legislation recently passed against the Indian communities of South Africa. The NIC argued that while they respected the royal family, they could not celebrate their visit because it would be counter to the objectives of the campaign. However, despite the NIC's constant calls for boycott, the Indian community came out in mass to celebrate the royal family's visit to Durban in March 1947. As a result, this article places the royal visit at the centre of the discussion about the divisions within the Indian community; divisions which led to the failure of Indian resistance movements in the late 1940s and early 1950s. I argue that this moment exemplifies the various ways individual South African Indians prioritised particular layers of their identity that were determinant in their decision to support or defy the political objectives of their leadership at the height of a mass resistance campaign.
Keywords: A.I. Kajee; Britse Ryk; Ghetto Act; Natal Indian Congress; Natalse Indiese Vereniging; koninklike besoek